Shale gas : exploration and environmental and economic impacts - Dayal, Anurodh Mohan; Mani, Devleena (Elsevier, 2017)
"Shale Gas: Exploration and Economic and Environmental Impacts is a guide to shale gas exploration for geoscientists, the oil and gas industry, and others with a vested interest in unconventional oil and gas development. Provides wide-ranging coverage of both the environmental and economic impacts of shale gas exploration; Includes case studies that describe the prolific and potential shale gas systems from both producing and prospective countries; Appeals to both those in academia and those in the unconventional gas exploration industry"--Back cover